Analisis Kadar Fenolik dan Flavonoid Ranting Pinus (Pinus merkusii Jungh. et de Vriese) dengan Spektrofotometri UV-Vis - Zulfisa Zulfisa; Trie Yuni Elfasyari; Reza Aprilia; Ahdi Dinil Haq. AH (Herbal Medicine Journal, 2026)
Pine twigs (Pinus merkusii Jungh. et de Vriese) remain an underexplored plant part regarding their secondary metabolite composition, although other parts such as leaves, flowers, and stem bark have been reported to contain phenolic and flavonoid compounds with antioxidant properties. This study aimed to determine the phenolic and flavonoid contents of ethanol extract derived from pine twigs using UVVis spectrophotometric analysis. The extract was obtained through maceration of dried twig powder using 96% ethanol. Phenolic content was determined using the FolinCiocalteu method with gallic acid as the reference standard, while flavonoid content was determined using the aluminum chloride (AlCl₃) colorimetric method with quercetin as the reference standard. Qualitative analysis confirmed the presence of phenolic and flavonoid compounds in the extract. The gallic acid calibration curve at a maximum wavelength of 783 nm yielded the regression equation ŷ = 0.09983 + 0.001394x with a correlation coefficient (r) of 0.9854 and coefficient of determination (R²) of 0.9710. Meanwhile, the quercetin calibration curve at 434 nm produced the regression equation ŷ = 0.01091 + 0.009805x with r = 0.9989 and R² = 0.9978. The phenolic content of pine twig extract was found to be 0.183% w/w, with a limit of detection (LOD) of 137.4666 µg/mL and a limit of quantification (LOQ) of 458.2217 µg/mL, whereas the total flavonoid content was 0.122% w/w, with an LOD of 3.9687 µg/mL and an LOQ of 13.2291 µg/mL. Precision analysis demonstrated good measurement repeatability. The findings indicate that pine twigs contain low but consistent levels of phenolic and flavonoid compounds, suggesting their potential as a natural source of bioactive compounds for further development, particularly following additional antioxidant activity studies.